Personal finance after 50 for dummies - Tyson, Eric (Eric Kevin); Carlson, Robert C., 1957- (--For dummies., 2021)
Retirement is lasting longer for all of us. That's why--and however long you decide to keep working--it's essential to plan ahead so you can live your post-career life as you wish. The latest edition of "Personal Finance After 50 For Dummies" details what you need to know--making it the perfect book to shelve next to your diet and fitness library, so you can keep your finances, as well as your health, in peak condition. Whether you're new to financial planning or are pretty savvy but want to cut through the noise with targeted information and advice, you'll find everything you need to know about how best to spend, invest, and protect your wealth so you can make your senior years worry-free, healthy, and fun. In plain English, retirement and financial experts Eric Tyson and Bob Carlson cover all the issues from investing, Social Security, and the long-term insurance marketplace to taxes and estate planning--including state-by-state differences. They demystify the muddy world of financial planning and provide strategies that make the course ahead crystal clear. They also dive into less obvious territory, showing how it's possible to strategize financially to avoid the worst impact of unexpected events--such as the COVID-19 crisis--as well as exploring what investment approaches you can take to protect the most important possession of all: your own and your family's health